Mycalamide A Shows Cytotoxic Properties and Prevents EGF-Induced Neoplastic Transformation through Inhibition of Nuclear Factors - Friedemann Honecker; Valentin A. Stonik; Carsten Bokemeyer; Larisa K. Shubina; Sergey A. Dyshlovoy; Anatoly I. Kalinovsky; Sergey N. Fedorov (Marine Drugs, 2012)
Mycalamide A, a marine natural compound previously isolated from sponges, is known as a protein synthesis inhibitor with potent antitumor activity. However, the ability of this compound to prevent malignant transformation of cells has never been examined before. Here, for the first time, we report the isolation of mycalamide A from ascidian Polysincraton sp. as well as investigation of its cancer preventive properties. In murine JB6 Cl41 P+ cells, mycalamide A inhibited epidermal growth factor (EGF)-induced neoplastic transformation, and induced apoptosis at subnanomolar or nanomolar concentrations. The compound inhibited transcriptional activity of the oncogenic nuclear factors AP-1 and NF-κB, a potential mechanism of its cancer preventive properties. Induction of phosphorylation of the kinases MAPK p38, JNK, and ERK was also observed at high concentrations of mycalamide A. The drug shows promising potential for both cancer-prevention and cytotoxic therapy and should be further developed.